2020
DOI: 10.14207/ejsd.2020.v9n1p173
|View full text |Cite
|
Sign up to set email alerts
|

The Problems in will Expression in Civil Law Transactions and Healthcare in Case of Capacity of Individuals

Abstract: The expression of each individual’s will is one of the important rights. This freedom is protected by human rights. In legal systems the expression of the central positions of the will of individuals is protected. In civil law transactions as well as in health care individuals have specific and complicated rights to express their will. And the problematics of it comes from that capacity issue. The rights to expression, rights to liberty ect. are recognized as the basic rights of each individual, of each member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Political stability is not synonymous with democracy; although the freedom of a state's citizens is often considered a key component of prosperity, it has historically been observed that the promotion of democracy, while an important value, does not necessarily lead to economic development (Lee, 2020). The will of each individual is an important right; this freedom is protected by human rights (Kudeikina and Palkova, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Political stability is not synonymous with democracy; although the freedom of a state's citizens is often considered a key component of prosperity, it has historically been observed that the promotion of democracy, while an important value, does not necessarily lead to economic development (Lee, 2020). The will of each individual is an important right; this freedom is protected by human rights (Kudeikina and Palkova, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The new Legal Profession Standard also includes the rights of a notary, which were not included in the previous professional standard. The RSU Faculty of Law has paid attention to the mentioned study course before (Kudeikina, Palkova, 2020).…”
Section: Covid-19 and Challenges In Providing Legal Educationmentioning
confidence: 99%
“…Only in limited cases is the treatment permitted without the patient's consent. 23 Th e Convention provides a broader mechanism for the national level or for the states to regulate the question on non-registered partners and patients' rights. Th ere are no strict restrictions for a particular group of people.…”
Section: Non-registered Partnerships From the Perspective Of Patients' Rightsmentioning
confidence: 99%